In vitro development of rifampicin resistance in the epithelial cells - Erokhina, M V; Aleksandrova, E A (Problemy tuberkuleza i bolezneĭ legkikh, 2006)
It has been first in vitro demonstrated on a model of epithelial cells that rifampicin may develop not only at the level of Mycobacterium tuberculosis, but also at the level of somatic cells. The mechanism of this phenomenon, its specificity (whether cross resistance to other antituberculous agents will occur), the way it puts into effect under the conditions of a microorganism, and how promptly it may be gone after discontinuation of the drug remain unknown. The effect of rifampicin on the functional activity of Pgp is an important factor that influences as a result not only the absorbability of drugs, but also normal transport processes in the body. These aspects seem to be topical and are the subject for further studies. The authors have obtained an epithelial cell line that resides in the presence of 100 microg/ml of rifampicin and that is 2-2.5 times more resistant to the drug as compared with the parental line. The cells of this line are 2-2.5 times more active in discharging the substrate rhodamine-123 for P-glycoprotein than those of the parental line, which suggests the enhanced functional activity of P-glycoprotein. The presence of P-glycoprotein in this line is confirmed by the action of this protein-specific blocker verapamil. At the same time rifampicin is not a substract for P-glycoprotein. Therefore, the mechanism of rifampicin resistance is unassociated with the functional activity of P-glycoprotein. The mechanism of the resistance remains open. At the same concentration (100 microg/ml), rifampicin can block the functional activity of P-glycoprotein. These results suggest the double mechanism of rifampicin in its long presence in the culture medium: as an inductor and a blocker of P-glycoprotein functional activity. The findings point to the fact that the pharmacokinetics of rifampicin and co-administered dtugs may change during their long use.